The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s1980-57642013dn70100008
|View full text |Cite
|
Sign up to set email alerts
|

Semantic memory: Nouns and action verbs in cognitively unimpaired individuals and frontotemporal lobar degeneration

Abstract: Among the instruments to evaluate semantic memory, the Pyramids and Palm Trees (PPT) and the Kissing and Dancing (KDT) tests are widely used but none have a performance referential for cognitively normal and impaired Brazilian populations.OBJECTIVE[A] To study these two tests in a sample of young healthy Brazilian individuals living in São Paulo; [B] To apply the results to the evaluation of two cases diagnosed with frontotemporal lobar degeneration.METHODSWe evaluated 50 normal participants (41 females and 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Our results corroborate the findings of Radanovic et al 33 who found no schooling effects for the Brazilian population with over 8 years of schooling on a comprehensive language test. It also confirms the reference values proposed by Mansur et al 11 for individuals with high education.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results corroborate the findings of Radanovic et al 33 who found no schooling effects for the Brazilian population with over 8 years of schooling on a comprehensive language test. It also confirms the reference values proposed by Mansur et al 11 for individuals with high education.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, even when removing the cards that caused more errors, schooling and, to a lesser degree age, remained significant covariates of performance. Moreover, when comparing our results to those obtained in the study of Mansur et al, 11 only five out of fifteen boards coincided among the ones that yielded more errors (items 8, 13 , 15 , 23 and 48). This inconsistency of performance among individuals needs to be analyzed further in order to decide whether items should be replaced or removed.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…A double dissociation may be postulated between PD patients and those exhibiting selective object-word deficits with relative preservation of action words and action semantics subsequent to posterior atrophy, as observed in Alzheimer's disease [36] and semantic dementia [37,38]. Furthermore, differential activations of frontal/prefrontal regions for verbs, and middle/posterior temporal regions for nouns, have been reported in neuroimaging studies with neurotypical native speakers of English [39,40], German [41], Italian [42], and Japanese [43].…”
Section: Action-language Impairments In Parkinson's Diseasementioning
confidence: 93%
“…A version of this task was created to assess reading (Rodrigues and Salles, manuscript submitted). In initial phases of research, instruments are available focusing on the assessment of semantic memory, such as the Cambridge semantic memory battery 65 used in patients with Primary Progressive Aphasia in Brazil 66 and the tests of semantic association Pyramids and Palm Trees, and Kissing and Dancing 67 instruments, have been investigated as relevant tools for the diagnosis of neurodegenerative syndromes such as primary progressive aphasia, particularly the semantic variant. 68 , 69 …”
Section: Current Panoramamentioning
confidence: 99%